y=2*2+3*2-6

Simple and best practice solution for y=2*2+3*2-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=2*2+3*2-6 equation:


Simplifying
y = 2 * 2 + 3 * 2 + -6

Multiply 2 * 2
y = 4 + 3 * 2 + -6

Multiply 3 * 2
y = 4 + 6 + -6

Combine like terms: 4 + 6 = 10
y = 10 + -6

Combine like terms: 10 + -6 = 4
y = 4

Solving
y = 4

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = 4

See similar equations:

| 5x+19=21+3x | | 10m-3m+1=22 | | fx=-3x^2+6x+8 | | 4x/6-7=3x/4+6 | | 9X-40=1 | | 2+3/x=2x/x-1 | | 15x^2-9x=94 | | X*2-14x+49=0 | | t^2-9+5=0 | | 9N^2-9N-28=0 | | 2x+8/3=-2 | | 3(2x+4)-3=16x+9-10x | | h/r=8/3.1459 | | 2x:7+15=17 | | -x+5=17 | | 2(u-9)=5u-36 | | 15x^3-9x=94 | | 2x^2+3=13 | | 5w+32=9(w+8) | | 5(x-1.5)=9.3 | | 2x+1*2x-3=4 | | 3f+3=11f-24 | | 5.7x-8.3=6.52 | | 6y-8x=40 | | -9(u-6)=2u+21 | | 10x=3x-35 | | 13y-1=4y+3 | | 10x+9x=608 | | 2x-(3x)=2 | | M^2-5M-84=0 | | 56.25k^2+1215k+45=0 | | 3=7x-3 |

Equations solver categories